2019
DOI: 10.1371/journal.pone.0222230
|View full text |Cite
|
Sign up to set email alerts
|

Post-exercise high-sensitivity troponin T levels in patients with suspected unstable angina

Abstract: BackgroundPrevious studies showed that troponin blood levels may increase after exercise. In this study we assessed whether, among patients admitted with suspected unstable angina, the increase in high-sensitive troponin T (hs-TnT) levels after exercise stress test (EST) might help identify those with obstructive coronary artery disease (CAD) and predict symptom recurrence during short term follow-up.MethodsMaximal treadmill EST was performed in 69 consecutive patients admitted to the emergency room with a sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 25 publications
3
14
0
Order By: Relevance
“…However, a higher myocardial work and oxygen consumption, as indicated by higher HR levels achieved during EST, tended to be associated with a higher TnI increase. Although not statistically significant, this finding is in agreement with a similar recent observation in patients admitted with a diagnosis of suspected unstable angina, 18 thus suggesting that myocardial metabolism is a major determinant of troponin release during exercise.…”
Section: Discussionsupporting
confidence: 91%
“…However, a higher myocardial work and oxygen consumption, as indicated by higher HR levels achieved during EST, tended to be associated with a higher TnI increase. Although not statistically significant, this finding is in agreement with a similar recent observation in patients admitted with a diagnosis of suspected unstable angina, 18 thus suggesting that myocardial metabolism is a major determinant of troponin release during exercise.…”
Section: Discussionsupporting
confidence: 91%
“…There was no difference in 4 hours postexercise cTnT concentrations between patients with unstable angina who did (n=23) or did not (n=46) develop recurrent angina at 6-month follow-up. 80 Another study reported no difference in the incidence of a composite end point (death, myocardial infarction, acute revascularization, hospitalization for unstable angina, or heart failure) in patients with CAD with 8 to 12 and 24-hour postexercise cTnI concentrations greater than versus less than the URL (27% versus 17%, P >0.05) during 36 (15–49) months of follow up. 81 The absence of an association of exercise cTn with subsequent symptoms may be attributable to the short duration of exercise, sample size, sampling times, only a small number of clinical events, or the absence of a clinically important relationship.…”
Section: Clinical Relevancementioning
confidence: 98%
“…However, cTn concentrations taken at rest in large populations and clinical studies predict mortality and cardiovascular morbidity, 2 , 4 even within the normal range. 3 The prognostic value of exercise-induced increases in cTn has rarely been studied 80 , 81 but may have clinical relevance in some populations as discussed later on in this article.…”
Section: Clinical Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…Although regular exercise reduces the risk of cardiovascular diseases, some studies have reported acute coronary syndrome and even sudden cardiac death related to sports activities (2). Some other studies have also reported elevations in cardiac damage biomarkers after prolonged exercise (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%